Proteome-Wide Analysis of Functional Divergence in Bacteria: Exploring a Host of Ecological Adaptations - FARES, MARIO ALI (My University, 2012)
Functional divergence is the process by which new genes and functions originate through the modification of existing ones. Both genetic and environmental factors influence the evolution of new functions, including gene duplication or changes in the ecological requirements of an organism. Novel functions emerge at the expense of ancestral ones and are generally accompanied by changes in the selective forces at constrained protein regions. We present software capable of analyzing whole proteomes, identifying putative amino acid replacements leading to functional change in each protein and performing statistical tests on all tabulated data. We apply this method to 750 complete bacterial proteomes to identify high-level patterns of functional divergence and link these patterns to ecological adaptations. Proteome-wide analyses of functional divergence in bacteria with different ecologies reveal a separation between proteins involved in information processing (Ribosome biogenesis etc.) and those which are dependent on the environment (energy metabolism, defense etc.). We show that the evolution of pathogenic and symbiotic bacteria is constrained by their association with the host, and also identify unusual events of functional divergence even in well-studied bacteria such as Escherichia coli. We present a description of the roles of phylogeny and ecology in functional divergence at the level of entire proteomes in bacteria.
PUBLISHED
Keywords: amino acid analysis; article; biogenesis; controlled study; convergent evolution; Escherichia coli; evolutionary adaptation; functional proteomics; genetic association; genetic conservation; genetic variability; host pathogen interaction; nonhuman; phylogeny; protein function; protein processing; ribosome; symbiosis; adaptation; bacterium; classification; cluster analysis; computer program; energy metabolism; metabolism; amino acid analysis; article; biogenesis; controlled study; convergent evolution; Escherichia coli; evolutionary adaptation; functional proteomics; genetic association; genetic conservation; genetic variability; host pathogen interaction; nonhuman; phylogeny; protein function; protein processing; ribosome; symbiosis; adaptation; bacterium; classification; cluster analysis; computer program; energy metabolism; metabolism